Mobile Robotics in Healthcare: Applications of Drones and Autonomous Vehicles for Medical Supply Delivery - Ushaa Eswaran (International Journal of Mobile Computing Technology, 2024)
This paper explores the transformative role of mobile robotics, specifically drones and autonomous vehicles, in enhancing healthcare delivery systems. As the demand for efficient medical supply logistics increases, these technologies present innovative solutions to overcome barriers in remote and underserved areas. We analyze various applications, including emergency medical deliveries, pharmaceutical transportation, and patient monitoring, highlighting the benefits of speed, cost-effectiveness, and reduced human intervention. Through case studies and experimental data, we demonstrate the operational effectiveness of these mobile robotics applications, illustrating their potential to revolutionize healthcare logistics.
Keywords: Healthcare; Logistics; Mobile robotics; Telemedicine; autonomous vehicles; drones; medical supply delivery; remote areas